PENGARUH KOMPENSASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA BISNIS LAUNDRY 99 DI KECAMATAN ARCAMANIK BANDUNG JAWA BARAT - Yunita Fourina Dewi (Jurnal Ekonomi dan Industri, 2021)
The purpose of this study was to determine how strong the influence of compensation and leadership style partially and simultaneously on employee performance at the Laundry Business 99 in Arcamanik District, Bandung, West Java. The research method used a survey with a quantitative approach that is correlational with the sampling technique is simple random sampling with the number of samples in this study were 28 respondents. Based on the results of the research that has been done, it can be concluded that: a) There is a positive and significant effect of compensation on employee performance, b) There is a positive and significant influence of leadership style on employee performance and c) There is a positive and significant influence on compensation and style joint leadership on employee performance at Laundry 99 Business in Arcamanik District, Bandung, West Java. This means that high compensation will be part of an effort to improve employee performance. A good leadership style is a style that is formed to foster clarity of goals and objectives, a work structure to achieve goals and objectives, and an effort to foster relationships between employees.